Readability and quality levels of websites that contain written information about lateral epicondylitis: A survey of Turkish websites (Annals of Medical Research, 2023)
Aim: This study aimed to evaluate the contents and readability levels of informational texts about lateral epicondylitis (LE) on Turkish websites.Materials and Methods: In this cross-sectional study, we performed online searches using the Turkish terms for 'lateral epicondylitis' and 'tennis elbow' on the Google, Yandex, and Yahoo search engines on May 8, 2022, and recorded the first ten pages of each search result. We classified the websites according to their sources. Group 1 was classified as websites prepared by private hospitals or medical centers, Group 2 as individual websites of orthopedic or physical therapists, and Group 3 as non-profit websites providing general health information that did not fall into the first two groups. Two reviewers analyzed the websites based on the website interface and the scoring for the LE content.Results: Among the 89 analyzed websites, there was no significant difference between the groups regarding Ateşman Readability Index scores. Group 1 got the highest score in terms of website content, closely followed by Group 2. The website content score of Group 3 was significantly lower than the other two groups (p< 0.05).Conclusion: The readability level of the texts on the informational Turkish websites related to LE is above the education level of our country. Further studies should be carried out on the propagation of internet accreditation systems, which aim to increase the reliability of the information on websites, also for Turkish websites. Accordingly, the development of future LE-related websites should comply with evidence-based guidelines and be written at an appropriate level to ensure the availability of reliable and understandable information for patients.
Keywords: Ateşman formula; Internet information; Lateral epicondylitis; Online search; Readability; Tennis elbow